The Role of e-Government in Bogor City’s Smart City Strategy toward SPBE Enhancement - Sri Nalendra, Muhammad Ariq; Rohimakumullah, Muhammad Al Assad (Jurnal Sosioteknologi, 2025)
The increase in the electronic-based government system (SPBE) has increased by 4% throughout 2024 in Bogor City, showing the success of Bogor City's smart city in the aspect of e-goverment. On the other hand, Bogor City also has many awards. Therefore, this research will analyze the smart city strategy through e-government as an example of digital services. This research employs a qualitative method with a constructivist paradigm and a case study approach as proposed by Creswell. The case analyzed represents a positive example of how Bogor City has successfully implemented its smart city initiatives through the concept of e-governance. Data in this study were collected through in-depth interviews with six participants, consisting of three key informants, two supporting informants, and one expert informant. Data were analyzed using thematic analysis with the assistance of NVivo software to construct an understanding of Bogor City’s e-government strategies in enhancing the SPBE implementation. This study indicates that the Government of Bogor City has effective strategies like (1) strategic orientation and stakeholder mapping, (2) substantive policy underpinnings, and (3) symbolic action and hooked tagline. Implementation in Bogor smart city is (1) urban infrastructure and experiential signals, (2) strategic publicity and digital presence, and (3) public opinion and responsive governance.